Enterprise innovation : from creativity to engineering - Missikoff, M.; Canducci, Massimo; Maiden, Neil (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2015)
"This book presents new methods and tools (from creativity to engineerying), aimed at promoting and sustaining enterprise innovaion and production improvement. The primary (but not exclusive) focus is on the new approaches, methods, frameworks and tools conceived for enterprise innovation and production improvement, developed during the European BIVEE Project (Business Innovation for Virtual Enterprise Ecosystems)"--Back cover
BIVEE Project Framing. Business Innovation in Virtual Enterprise Environments / Massimo Canducci -- From Creativity to Innovation: The Importance of Design / Neil Maiden -- The BIVEE Project: An Overview of Methodology and Tools / Michele Missikoff, Pierluigi Assogna -- Storytelling on BIVEE Experience. A Project of Collaborative Networked Innovation / Cristina Cristalli, Daniela Isidori, Isabella Terzoni -- A Day of Networked Production Improvement / Fernando Gigante Valencia, Anil Pacaci, Ali Anil Sinaci -- Innovating Innovation: BIVEE Achievements. The BIVEE Framework and the Collaborative Innovation Capability Maturity Model (CICMM) / Benjamin Knoke -- The BIVEE Environment: Description of the Overall Software Architecture / Mauro Isaja -- The Mission Control Room / Nesat Efendioglu, Wilfrid Utz, Robert Woitsch -- The Virtual Innovation Factory / Francisco Calle Moreno -- The Production and Innovation Knowledge Repository / Francesco Taglino, Fabrizio Smith -- Monitoring Innovation and Production Improvement / Claudia Diamantini, Domenico Potena, Emanuele Storti -- Raw Data Connection Services and Tools / Mauro Isaja -- Concrete Experience of Innovation in a Knowledge Centric Economy. Innovation and Production Improvement in Virtual Enterprises: The User Perspective / Anil Pacaci, Ali Anil Sinaci, Asuman Dogac -- A Methodology for the Setup of a Virtual Innovation Factory Platform / Cristina Cristalli, Daniela Isidori, Isabella Terzoni -- The AIDIMA Experience / Fernando Gigante Valencia.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed August 13, 2015).
John Wiley and Sons
Keywords: Technological innovations -- Management; Innovations -- Gestion; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Technological innovations -- Management; Forschung und Entwicklung